REACTIONS AND RESPONSES OF THE CHRISTIAN DEMOCRATS PARTY AGAINST THE MILITARY COUP OF 1973: ¿COLLABORATION OR OPPOSITION? - Rubio Apiolaza, Pablo; Torres Dujisin, Isabel (Revista de Historia Social y de las Mentalidades, 2024)
This article presents an analysis of the political strategy of the Christian Democratic Party (PDC) during the first year of the Chilean military dictatorship. It emphasizes its policy of alliances and internal relations, selecting some key junctures in its relationship with the Popular Unity and its reaction to the Military Coup and the first year of the dictatorship. Through a review of its internal documentation, the article seeks to demonstrate the dominance of conservative positions DC, even though the party positions are not unique, which explains an intense internal debate at the beginning of the dictatorship.